Production of Alkaline Protease by Solvent-Tolerant Alkaliphilic Bacillus circulans MTCC 7942 Isolated from Hydrocarbon Contaminated Habitat: Process Parameters Optimization. (28th November 2013) - Patil, Ulhas; Chaudhari, Ambalal
Abstract : In the present investigation, a newly isolated organic solvent-tolerant and alkaliphilic bacterial strain was reported from a hydrocarbon (gasoline and diesel) contaminated soil collected from the petrol station, Shirpur (India). The strain was identified as Bacillus circulans MTCC 7942, based on phenotype, biochemical, and phylogenetic analysis of 16S rRNA gene sequence. The capability of Bacillus circulans to secrete an extracellular, thermostable, alkaline protease and grow in the presence of organic solvents was explored. Bacillus circulans produced maximum alkaline protease (412 U/mL) in optimized medium (g/L): soybean meal, 15; starch, 10; KH2 PO4, 1; MgSO4 ·7H2 O, 0.05; CaCl2, 1; Na2 CO3, 8; pH 10.0 at 37°C and 100 rpm. The competence of strain to grow in various organic solvents— n -octane, dodecane, n -decane, N, N-dimethylformamide, n -hexane, and dimethyl sulfoxide, establishes its potential as solvent-stable protease source for the possible applications in nonaqueous reactions and fine chemical synthesis.